Estimation of the absorption of extraterrestrial radio noise using a narrow beam VHF radar at 53.5 MHz in Andenes, Norway - Sadeghi, Seyed Soheil (Chalmers tekniska högskola / Institutionen för radio- och rymdvetenskap, 2008)
The Earth’s magnetic field works like a shield against the solar wind flux of plasma, but at the polar regions, where it fails to do so, these charged particles may be guided down to low altitudes and introduce a lot of impacts on the environment, ranging from the nice colourful Aurora, to chemical changes in the atmosphere and decrease in the amount of ozone in the middle atmosphere, and from satellite damages to power line cut offs, depending on the type and energy of the particles. Extraterrestrial HF/VHF radio noise from the universe and mainly from our own galaxy is continuously coming towards our planet. Absorption of these electromagnetic waves in the Earth’s ionosphere is a well known proxy of the events which can enhance it, mainly having direct or indirect root in the solar activities, like Solar Flares, Coronal Mass Ejections, and Geomagnetic Storms and the resulted X rays, Solar Proton Events and Precipitating Energetic charged Particles. Cosmic radio noise power and the corresponding ionospheric absorption is normally measured by the riometers (Relative Ionospheric Opacity Meters for Extraterrestrial Electromagnetic Radiation), and especially in recent years by multiple narrow beam imaging riometers. In this thesis, the data obtained by the vertical beam of a narrow beam MST radar, ALWIN, at Andenes, Norway (69.17°N; 16.01°E) is used as a (narrow beam of a) riometer to estimate the incident cosmic noise power at 53.5 MHz and its absorption, especially during solar/geomagnetic activity periods. The results are in good agreement with riometers (IRIS and AIRIS in Andenes and Kilpisjarvi Finland, 69.06°N, 20.55°E) common volume measurements and with electron density measurements of the Saura MF Radar. The obtained Quiet Day Curves (QDCs) are in very good agreement with theoretical and observed QDCs estimated by Friedrich et al. (2001).